2018
DOI: 10.1016/j.coviro.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

All-atom virus simulations

Abstract: The constant threat of viral disease can be combated by the development of novel vaccines and therapeutics designed to disrupt key features of virus structure or infection cycle processes. Such development relies on high-resolution characterization of viruses and their dynamical behaviors, which are often challenging to obtain solely by experiment. In response, all-atom molecular dynamics simulations are widely leveraged to study the structural components of viruses, leading to some of the largest simulation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 154 publications
(175 reference statements)
0
27
0
Order By: Relevance
“…All-atom MD simulations of viruses 147 149 — which have also been used to study the permeability of poliovirus capsids to water 150 and the binding of ions to HIV-1 capsids 146 , for example — indicate that mutated capsids may collapse because of thermal fluctuations 151 . Relatedly, Brownian dynamics simulations of a coarse-grained representation of capsids revealed that they can melt, crumple or collapse under the action of thermal fluctuations, depending on the materials properties of the shell 152 (Fig.…”
Section: Dynamics Of Closed Shellsmentioning
confidence: 99%
“…All-atom MD simulations of viruses 147 149 — which have also been used to study the permeability of poliovirus capsids to water 150 and the binding of ions to HIV-1 capsids 146 , for example — indicate that mutated capsids may collapse because of thermal fluctuations 151 . Relatedly, Brownian dynamics simulations of a coarse-grained representation of capsids revealed that they can melt, crumple or collapse under the action of thermal fluctuations, depending on the materials properties of the shell 152 (Fig.…”
Section: Dynamics Of Closed Shellsmentioning
confidence: 99%
“…To test the hypothesis that IPs and other metabolites modulate the translocation of dNTPs through CA oligomers, we have employed a multipronged approach combining all-atom molecular dynamics (MD) simulations [ 19 ], atomic force microscopy (AFM), transmission electron microscopy (TEM), confocal microscopy, and virus infectivity assays. Additionally, we have analyzed the effect of IP 6 on HIV-1 capsid stability and reverse transcription and determined the molecular mechanism that regulates translocation of dNTPs through the capsid.…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecular containers are essential biological machines, whose study is critical to understanding the living cell. Containers such as enveloped virions [5,6], organelles [4,57], and potentially even minimal cells will no doubt be among the major systems investigated with MD simulations on upcoming exascale supercomputing platforms, which will enable calculations encompassing billions of particles. Beyond enabling new scientific discoveries, large-scale MD simulations will continue to drive the development of novel technologies to overcome the challenges of working with big datasets [13,58].…”
Section: Resultsmentioning
confidence: 99%